Exploring the relationship between land characteristics and the sustainable growth of coconut cultivation in Indonesia - Vaulina, Sisca; Titisari, Prima Wahyu; Elinur; Zahrah, Siti; Dewi, Ilma Satriana (Asian Journal of Agriculture and Rural Development, 2024)
This study explores land types as a basis for evaluating the sustainability of coconut plantations in Indonesia, focusing on peatlands and coastal areas that affect productivity and management practices. This research aims to evaluate the sustainability of coconut plantation farming across various land types and identify critical sustainability factors. Carried out in Indragiri Hilir Regency, Riau Province, the study employed a survey methodology and utilized Rap-Coconut Ordination Analysis coupled with Multidimensional Scaling (MDS). The surveyed area encompasses peatlands and coastlands, and a purposive sampling approach, guided by the Slovin Formula, yielded a sample size of 101 coconut farmers. The sustainability assessment covered five dimensions: ecological (7 attributes), social-cultural (4 attributes), economic (4 attributes), technological (6 attributes), and institutional (7 attributes) and 28 attributes. The study assessed the sustainability of coconut farming in Indragiri Hilir Regency, Riau Province. Peatlands showed lower sustainability, while coastline lands demonstrated higher sustainability levels. Key factors affecting sustainability include ecological aspects like fertilizer and pesticide use, socio-cultural elements like family involvement and attitudes towards coconut farming, economic factors like the coconut vending system, technological considerations such as optimal planting spacing and seed quality, and institutional factors like participation in extension programs and access to financial resources.